Identifying Strengths and Gaps in Data Management and Reporting through Malaria Routine Data Quality Assessment: Results from Two Health Regions in Madagascar - Yé, Maurice; N'Gbichi, Jean Marie; Andrianantoandro, Tokinirina; Rabesahala, Sabas; Rabibizaka, Urbain; Ramiranirina, Brune Estelle; Rabeola, Omega; Kapesa, Laurent; Yé, Yazoumé (The American journal of tropical medicine and hygiene, 2025)
In 2021, the U.S. President's Malaria Initiative Measure Malaria project provided support to the National Malaria Program to conduct a data quality assessment. The main goal was to help health centers enhance the quality of their malaria data. The assessment involved reviewing data from outpatient registers, monthly reports, and DHIS2 data. Reporting timeliness, completeness, data element completeness, and availability of source documents were assessed. For timeliness, the assessment measured the proportion of reports that were submitted on time out of the expected total. The results showed that the reporting timeliness was inadequate in Atsinanana (85%) and adequate for Atsimo-Andrefana (95%). Data elements completeness, which refers to reports without missing data, was inadequate in Atsinanana (43%) and Atsimo-Andrefana (68%). The availability of source documents, such as records forms, was assessed and found to be 59% in Atsimo-Andrefana and 48% in Atsinanana. The use of standard reporting forms, which ensures consistency and accuracy in reporting, was reported to be 44% in Atsinanana and 54% in Atsimo-Andrefana. Data discrepancies were identified between outpatient registers, monthly reports, and DHIS2 data. A verification factor (VF) was used to compare the figures in these different sources. The VF was 1.2 in Atsinanana and 1.1 in Atsimo-Andrefana for both monthly reports and DHIS2 data, indicating an overreporting of fever cases tested in 6- to 13-year-olds. Overall, the assessment revealed gaps in data elements completeness, reporting accuracy, and availability of data recording guidelines. The findings suggest that regular data quality assessments should be implemented to guide decision making in Madagascar.